2013
DOI: 10.1124/mol.113.086322
|View full text |Cite
|
Sign up to set email alerts
|

Arginine Vasopressin Enhances Cell Survival via a G Protein–Coupled Receptor Kinase 2/β-Arrestin1/Extracellular-Regulated Kinase 1/2–Dependent Pathway in H9c2 Cells

Abstract: Circulating levels of arginine vasopressin (AVP) are elevated during hypovolemia and during cardiac stress. AVP activates arginine vasopressin type 1A (V 1A )/Ga q -coupled receptors in the heart and vasculature and V 2 /Ga s -coupled receptors in the kidney. However, little is known regarding the signaling pathways that influence the effects of V 1A receptor (V 1A R) activation during cellular injury. Using hypoxia-reoxygenation (H/R) as a cell injury model, we evaluated cell survival and caspase 3/7 activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 39 publications
2
24
0
1
Order By: Relevance
“…Taken together these data suggest that changes in GRK5 are associated with the pathophysiology of severe neuropsychiatric illnesses associated with cognitive impairment. GRK5 abnormalities are also associated with cocaine administration, major depressive disorder, as well as behavioral hypersensitivity, consistent with the central role(s) of this molecule for linking GPCR activation with intracellular signaling processes (Bychkov et al, 2011a; Erdtmann-Vourliotis et al, 2001; Franklin and Carrasco, 2013; Gainetdinov et al, 1999; Ji et al, 2013; Kara et al, 2006; Luo et al, 2008; Ren et al, 2005; Shenoy et al, 2006; Zheng et al, 2012; Zhu et al, 2004; Zhu et al, 2013). …”
Section: 1 Discussionmentioning
confidence: 64%
“…Taken together these data suggest that changes in GRK5 are associated with the pathophysiology of severe neuropsychiatric illnesses associated with cognitive impairment. GRK5 abnormalities are also associated with cocaine administration, major depressive disorder, as well as behavioral hypersensitivity, consistent with the central role(s) of this molecule for linking GPCR activation with intracellular signaling processes (Bychkov et al, 2011a; Erdtmann-Vourliotis et al, 2001; Franklin and Carrasco, 2013; Gainetdinov et al, 1999; Ji et al, 2013; Kara et al, 2006; Luo et al, 2008; Ren et al, 2005; Shenoy et al, 2006; Zheng et al, 2012; Zhu et al, 2004; Zhu et al, 2013). …”
Section: 1 Discussionmentioning
confidence: 64%
“…In the previous study we have shown that AVP (0.03 mg/rat) has protective effects on ischemia/reperfusion (I/R) induced myocardial injury in rat heart (Nazari et al, 2011). Interestingly, other study confirmed the protective effects of AVP in low dose on myocardial injury of the ischemic reperfused heart (Pelletier et al, 2013;Zhu et al, 2013). Also vasopressin infusion is cardioprotective in models of myocardial ischemia (Okamura et al, 1999) and in patients with postcardiotomy shock (Dunser et al, 2002).…”
Section: Introductionmentioning
confidence: 79%
“…Vasopressin or arginine vasopressin (AVP) is essential for cardiovascular homeostasis (Holmes et al, 2001). Circulating levels of AVP, which are elevated during hypovolemia and during cardiac stress, mediate important physiological functions such as osmotic regulation, vasoconstriction, and release of adrenocorticotropic hormone (ACTH) (Zhu et al, 2013). In the previous study we have shown that AVP (0.03 mg/rat) has protective effects on ischemia/reperfusion (I/R) induced myocardial injury in rat heart (Nazari et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…The next complex signaling pathway analyzed was D2R-mediated ERK phosphorylation. b-Arrestins are involved in ERK phosphorylation downstream of several GPCRs (Lefkowitz and Shenoy, 2005;Zhu et al, 2013). However, it has been suggested that the D2R-mediated ERK phosphorylation is a G protein-mediated event that is not dependent on b-arrestins (Quan et al, 2008).…”
Section: Ligand Bias For Immediate and Complex Effectorsmentioning
confidence: 99%